2020
DOI: 10.25157/jkg.v2i2.4532
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Faktor Determinan Penyakit Infeksi Saluran Pernapasan Akut (Ispa) Dengan Kejadian Inpeksi Saluran Pernafasan Akut (Ispa) Pneumonia Pada Balita Di Wilayah Kerja Puskesmas Cipaku Kabupaten Ciamis Tahun 2020

Abstract: Pneumonia adalah bentuk infeksi pernapasan akut yang menyerang paru-paru. Paru-paru terdiri dari kantung-kantung kecil yang disebut alveoli, yang terisi udara ketika orang sehat bernafas. Ketika seseorang menderita pneumonia, alveoli dipenuhi dengan nanah dan cairan, yang membuat pernafasan terasa menyakitkan dan membatasi asupan oksigen (WHO,2019). Metode yang digunakan dalam penelitian ini adalah metode deskriptif korelasi dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh Ibu ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…However, the study's results found that it is not in line with the poor knowledge of most mothers in high maternal education. The results of this study are supported by Wibowo & Ginanjar (2020) with a value (p-value = 0.94 > 0.05), which means there is no significant relationship between maternal education and the incidence of ARI in toddlers in the Cipaku Health Center working area (28).…”
Section: Variablesupporting
confidence: 67%
“…However, the study's results found that it is not in line with the poor knowledge of most mothers in high maternal education. The results of this study are supported by Wibowo & Ginanjar (2020) with a value (p-value = 0.94 > 0.05), which means there is no significant relationship between maternal education and the incidence of ARI in toddlers in the Cipaku Health Center working area (28).…”
Section: Variablesupporting
confidence: 67%
“…This study is in line with research conducted at the Bahu Health Center in Manado City, which showed that there was a relationship between the level of knowledge and the incidence of pneumonia in toddlers. 5 Mothers who have good knowledge tend to show good pneumonia prevention behavior, while mothers who have sufficient knowledge and less tend to show sufficient pneumonia prevention behavior. 10 Through knowledge, humans can make qualitative changes to individuals so that their behavior develops.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of pneumonia includes eliminating air pollution, especially indoors, early detection, and adequate treatment of pneumonia. 4,5 Pneumonia has risk factors such as malnutrition, lack of exclusive breastfeeding, incomplete measles immunization, premature birth, low family economic status, comorbid conditions, unaffordable access to health services, population density, bringing children to the kitchen while cooking, and status malnutrition. [6][7] Based on data from the Banda Aceh City Health Office, the prevalence of acute respiratory infections (ARI) in 2012 was 50.91% and in 2013 was 47.8%, the first highest number of 10 types of infectious diseases.…”
mentioning
confidence: 99%
“…Lebih dari separuh balita dengan ISPA dalam penelitian ini berjenis kelamin perempuan yaitu sebanyak 78 balita (53,4%) dibandingkan dengan jenis kelamin laki-laki sebanyak 68 balita (46,6%). Hasil penelitian ini sama dengan yang dilakukan oleh Wibowo & Ginanjar (2020) bahwa sebanyak 41 balita (41%) perempuan dan 26 balita (26%) yang mengalami ISPA [21]. Hasil penelitian lain mengatakan hal yang sama yang dilakukan oleh Yanti & Sari (2018) di Wilayah Kerja Puskesmas Sukaraja Nuban Kabupaten Nuban Kabupaten Lampung Timur sebanyak 44 (57,9%) responden balita perempuan dan 40 (70,2%) responden balita laki-laki mengalami ISPA [14].…”
Section: Jenis Kelaminunclassified